Evaluation of Dynamic Corneal Response Parameters and the Biomechanical E-Staging After Accelerated Corneal Cross-Linking in Keratoconus. Issue 6 (7th November 2022) - Flockerzi, Elias; Xanthopoulou, Kassandra; Daas, Loay; Feld, Simon; Langenbucher, Achim; Seitz, Berthold
Abstract : Purpose: This study evaluated the biomechanical E-staging in progressive keratoconus (KC) corneas before and after epithelium-off accelerated corneal cross-linking (CXL, 9 mW/cm 2, 10 min, 5.4 J/cm 2 ). Design: German university-based retrospective longitudinal cohort study. Methods: The biomechanical E-staging for ectatic corneal diseases was applied retrospectively on 49 progressive KC corneas of 41 patients who underwent CXL. Main outcome parameters included the Corvis Biomechanical Factor (CBiF, the linearized Corvis Biomechanical Index), the biomechanical E-staging (E1 to E4 result of dividing the CBiF value range into 5 groups), maximal anterior keratometry (Kmax), anterior radius of curvature (ARC), and thinnest corneal thickness (TCT). They were evaluated at 2.1±2.0 months preoperatively (n=49 corneas, 41 patients) and postoperatively after 5.4±1.4, 11.3±1.8, and 23.4±1.6 months. Results: The CBiF decreased (5.1±0.5 | 5.0±0.5, P =0.0338) and the E-staging increased significantly (2.4±0.9 | 2.6±0.8, P =0.0035) from preoperatively to the first postoperative follow-up. The difference was not significant after 11 months and there were same values after 23 months. Kmax, ARC, and TCT slightly decreased (Kmax: 56.9±6.3, 54.3±5.1, 56.2±6.6, 54.0±5.2; ARC: 49.8±3.5, 48.9±3.2, 50.8±5.6, 49.0±3.7; TCT: 470±34, 454±36, 459±35, 466±39; preoperatively and 5, 11, and 23 months postoperatively). A postoperatively decreased TCT was associated with an increased E-stage, whereas an equal or increased TCT measurement after CXL was associated with equal or lower E-staging results. Conclusions: The biomechanical E-staging in KC corneas is influenced by TCT measurements and increases within the first postoperative months after CXL. On the long term, it indicates a postoperative KC stabilization, with comparable E-values to preoperatively at 11 and 23 months after CXL.